2009
DOI: 10.1103/physrevb.80.014203
|View full text |Cite
|
Sign up to set email alerts
|

Structure investigation of the (100) surface of the orthorhombicAl13Co4crystal

Abstract: We present a detailed study of the ͑100͒ surface of the orthorhombic Al 13 Co 4 crystal using both experimental and ab initio computational methods. This complex metallic alloy is an approximant of the decagonal Al-Ni-Co quasicrystalline phase. After sputter-annealing preparation of the surface at 1073 K, the low-energy electron diffraction pattern recorded exhibits a pseudotenfold symmetry with lattice parameters consistent with those of the bulk model. At this stage, scanning tunneling microscopy ͑STM͒ measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
51
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 45 publications
11
51
1
Order By: Relevance
“…Earlier studies of the (100) surface based on both experimental (STM, XPS, and dynamical LEED) and ab initio studies using density functional theory (DFT) have shown that the surface terminates at incomplete P layers. 16,17 The best agreement is found for the P termination models that have all 22 Al atoms per surface unit cell present, but with all 4 Co atoms per unit cell missing. Aside from these missing atoms, the surface structure is similar to that of the corresponding bulk planes, with only a small amount of relaxation in the surface layers as determined by LEED.…”
Section: A Main Features Of the Clean Surfacesupporting
confidence: 52%
“…Earlier studies of the (100) surface based on both experimental (STM, XPS, and dynamical LEED) and ab initio studies using density functional theory (DFT) have shown that the surface terminates at incomplete P layers. 16,17 The best agreement is found for the P termination models that have all 22 Al atoms per surface unit cell present, but with all 4 Co atoms per unit cell missing. Aside from these missing atoms, the surface structure is similar to that of the corresponding bulk planes, with only a small amount of relaxation in the surface layers as determined by LEED.…”
Section: A Main Features Of the Clean Surfacesupporting
confidence: 52%
“…It has some atoms missing, but the remaining atoms essentially retain the bulk arrangement [17; 18].) In Al 13 Co 4 (100) the two types of terraces alternate laterally on the surface, separated by steps of a single height [17]. Both the alternation and the step height are consistent with the stacking of Alrich layers in the bulk structure.…”
Section: Discussionsupporting
confidence: 48%
“…In Al 13 Co 4 (100), one type of terrace disappears upon extended annealing at elevated temperature, so the other must be the less-stable termination [17]. In our experiments, we did not observe that one terrace disappears systematically with increasing temperature, but an indication of this type of evolution may be the bumps on the B-terraces.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Perhaps most striking is a series of studies of Al13Co4(100) [44,48,49], in which three different samples yielded three different surface structures, even though the surfaces were prepared in very similar fashion. Furthermore, the stability range of bulk Al13Co4 spans only 0.5 at%, so any differences in bulk composition must have been very small.…”
Section: Discussionmentioning
confidence: 99%